Nursing: An essential expression of human endeavour - P.H. Harrison (AOSIS, 1982)
To put nursing into some sort of perspective a brief historical journey is called for. History allegedly helps us to understand the present and even forecast the future through an awareness of past errors. Much depends on one's source materials and it is very often a purely subjective approach that is presented in certain records and journals which in turn will influence the writings of the present-day reviewer of past events. So can one really produce a totally objective study of nursing and nurses in past centuries?